Schmutzi: estimation of contamination and endogenous mitochondrial consensus calling for ancient DNA. Issue 1 (December 2015) - Renaud, Gabriel; Slon, Viviane; Duggan, Ana; Kelso, Janet
Abstract Ancient DNA is typically highly degraded with appreciable cytosine deamination, and contamination with present-day DNA often complicates the identification of endogenous molecules. Together, these factors impede accurate assembly of the endogenous ancient mitochondrial genome. We present schmutzi, an iterative approach to jointly estimate present-day human contamination in ancient human DNA datasets and reconstruct the endogenous mitochondrial genome. By using sequence deamination patterns and fragment length distributions, schmutzi accurately reconstructs the endogenous mitochondrial genome sequence even when contamination exceeds 50 %. Given sufficient coverage, schmutzi also produces reliable estimates of contamination across a range of contamination rates. Availability:https://bioinf.eva.mpg.de/schmutzi/ license:GPLv3.